The Relationship Between Body Mass Index and Student Body Ability Index of Medical Faculty Jember University - Adelia Handoko; Aris Prasetyo; Pipiet Wulandari; Kristianingrum Dian Sofiana; Jauhar Firdaus; Karisma Adya Pertiwi (Faculty of Medicine, University of Jember, 2021)
Technological advances in recent years have had an impact on people's lifestyles. Almost all activities in various sectors can be carried out and accessed via smartphones. This causes a decrease in physical activity which can lead to obesity. Obesity is an imbalance of energy entering the energy used in the body resulting in the accumulation of excess lipids which can interfere with the health condition of the body. Body composition is an important part of determining one's physical fitness. Body composition can be seen from a person's Body Mass Index (BMI). This type of research is analytic observational with cross sectional research design. The data used by researchers is secondary data in 2018. The sampling technique used is purposive sampling. The sample used in this study was 127 people, consisting of 47 men and 84 women. Data were analyzed using SPSS version 26 through the Spearman Analysis Test with the results of p = 0.000 (p-value <0.05) for the relationship between BMI and IKB in the slow way and p = 0.002 (p-value <0.05) for the relationship between BMI with IKB the fast way. The conclusion that can be drawn from the results of the analysis is that there is a weak correlation between body mass index and body fitness index on the Havard Step Test fitness test for students of the Faculty of Medicine, University of Jember. Keywords: body mass index, harvard step test , physical fitness